“Stark Raving Sane”: A Deconstructionist Reading of Tom Stoppard’s Rosencrantz and Guildenstern Are Dead - MOOSAVINIA, Sayyed Rahim; RAEISI, Fatameh (Anafora, 2023)
The focus of this study is the theme of Hamlet’s madness in Tom Stoppard’s Rosencrantz and Guildenstern Are Dead, which as a play based on Shakespeare’s Hamlet, provides a critique on this theme through the perspective of Ros and Guil, who, by means of a reversal of minor and major characters, have become the center of the spotlight in Stoppard’s play. The concept of madness in general is complicated, including many different aspects, among which the historical aspect is the most significant, as the definition of madness has evolved through different historical eras. By placing Stoppard’s Rosencrantz and Guildenstern Are Dead in a historical context, this essay aims to demonstrate that as a play written in the latter half of the twentieth century, Ros and Guil’s critique of Hamlet’s madness, with all the intricacies of its language, collapses the binary opposition of sanity and insanity in a twentieth century poststructuralist manner, and leads to no clear-cut answer to the question of Hamlet’s madness. However, as a play whose events unfold in the context of Hamlet, a Renaissance play, it carries some of the social and political aspects of Shakespeare’splay, as Ros and Guil’s evaluation of Hamlet’s condition is heavily under Claudius’s politically infused influence.